Validation of the Wijma delivery expectancy/experience questionnaire for pregnant women in Malawi: a descriptive, cross-sectional study - Madalitso Khwepeya; Hui-Chuan Huang; Gabrielle T. Lee; Shu-Yu Kuo (BMC, 2020)
Abstract Background Fear of childbirth is a common health concern for women during pregnancy. The Wijma Delivery Expectancy/Experience Questionnaire (W-DEQ) is widely used to measure childbirth fear during pregnancy. However, this instrument is yet to be validated in Malawi, Africa. Our study aimed to assess the psychometric properties of the W-DEQ questionnaire in Malawi. Methods Healthy pregnant women in the third trimester (N = 476) at a district hospital in Malawi were included. Fear of childbirth, depressive symptoms, and quality of life were assessed using the W-DEQ, the Edinburg Postnatal Depression Scale, and the World Health Organization Quality of Life scale, respectively. The construct validity, reliability, and convergent validity of the W-DEQ were examined using exploratory and confirmatory factor analyses, Cronbach's alpha, and Pearson correlations. Results The mean age of participants was 28.2 (standard deviation = 6.8) years. Exploratory and confirmatory factor analysis of the Malawian version of the W-DEQ indicated a multidimensional structure with three factors: fear, negative appraisal, and a lack of self-efficacy, with acceptable goodness of model fit. The Malawian version of the W-DEQ showed a satisfactory internal consistency (α = 0.84) and was significantly correlated with depressive symptoms (r = 0.23, p < 0.001) and quality of life (r = − 0.17 ~ -0.26, ps < 0.05). Conclusions Our findings support the Malawian W-DEQ version being a reliable and valid instrument for measuring childbirth fear in African women.